The Two Sector Growth Model with Fixed Coefficients - Corden, W. M. (Review of Economic Studies, 1966)
Journal Article The Two Sector Growth Model with Fixed Coefficients Get access W. M. Corden W. M. Corden Australian National University, Canberra Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 3, July 1966, Pages 253–262, https://doi.org/10.2307/2974419 Published: 01 July 1966